2021
DOI: 10.37394/232015.2021.17.75
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Home Food Gardening Program to Household Food Security in Indonesia: A Review

Abstract: Home gardens are an essential component of the local food system and family farming worldwide. In Indonesia, a home food gardening program was initiated in the early 2010s to optimally utilize home yards for improving the adequacy of food consumption and nutrition intake of households. In the present challenging situation of Covid-19 pandemic, there has been a growing interest in home gardens to help mitigate food insecurity caused by food supply chain disruptions and the emergence of physical and economic bar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 97 publications
0
13
0
5
Order By: Relevance
“…However, not for all categories of food security positive associations were found, that is, availability and access (Dillon et al, 2018). A recent study from India showed positive effects of home gardens on food security in terms of food availability, access, and utilization but found no improvement in terms of food stability (Saediman et al, 2021). For diet quality and nutritional status of women and children, the present review shows positive impacts of home gardens for Burkina Faso and contrasting findings for Kenya.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, not for all categories of food security positive associations were found, that is, availability and access (Dillon et al, 2018). A recent study from India showed positive effects of home gardens on food security in terms of food availability, access, and utilization but found no improvement in terms of food stability (Saediman et al, 2021). For diet quality and nutritional status of women and children, the present review shows positive impacts of home gardens for Burkina Faso and contrasting findings for Kenya.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, diversified home gardens provide an opportunity to buffer the quantitative harvest losses and the qualitative nutrient dilution in major staple crops, which are the consequences of climate change-related weather phenomena and increased ambient CO 2 concentrations, respectively (Myers et al, 2017). The limited effects of home gardening on nutritional status found by previous studies have been attributed to short intervention periods, low participation rates, and insufficient setup of home gardens (Kumar et al, 2018;Olney et al, 2015;Saediman et al, 2021). Kumar et al (2018) hypothesized that education, information, and market linkage could assist households in increasing their horticultural production and improving their nutrition.…”
Section: Nutrition and Health Sustainability Of Home Gardensmentioning
confidence: 99%
“…In addition to the main staple foods of rice, corn, sweet potatoes and sweet potatoes, other foodstuffs are still consumed by some communities, such as sago. Rice Production in Indragiri Hilir Regency in 2015 for rice fields and rice fields amounted to 111,318 and 949.19 tons, among them [22], [23], [28]- [30].…”
Section: Food Availabilitymentioning
confidence: 99%
“…It can cause food insecurity, unemployment, and poverty [2,3]. This condition is exacerbated by the Covid-19 pandemic, which has affected all sectors of the economy as a result of the implementation of social distancing and lockdowns, thus disrupting the food supply system, which can exacerbate malnutrition and malnutrition due to increasingly limited access to food [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%